Oxylipins in the yeast genus Ascoidea - Ncango, Desmond Mbulelo (University of the Free State, 2007)
Acetylsalicylic acid (ASA)-sensitive 3-hydroxy (3-OH) oxylipins were uncovered in 1991 in the yeast Dipodascopsis uninucleata. Since then, various similar oxylipins were found to be widely distributed in fungi. Interestingly, 3-OH oxylipins were reported to play a role in ascospore release from enclosed asci, where they are involved in assisting nano-scale gear-like (D. uninucleata); sliding (Dipodascus); drilling (Eremothecium sinecaudum) and piercing movements (E. ashbyi and E. coryli). In Ascoidea africana, a 3- OH 10:1 oxylipin was found to be associated with hat-shaped ascospores carried inside ellipsoidal asci. However, in this study no function was proposed for this oxylipin. Since only one species representing the genus Ascoidea was studied, it became the aim to further expand this study to also include A. corymbosa and A. rubescens. Using confocal laser scanning microscopy (CLSM) on cells stained with fluorescein-coupled 3-OH oxylipin specific antibodies, this study suggests that oxylipins are specifically associated with ascospores and not vegetative cells of A. corymbosa and A. rubescens. Using gas chromatography - mass spectrometry (GC-MS) the oxylipin, 3-OH 17:0, was identified in A. corymbosa. Here, oxylipin-coated razor sharp ascospore brims may play a role in rupturing the ascus to affect forced release of hat-shaped ascospores. Literature suggests that 3-OH oxylipins are produced by β-oxidation or fatty acid synthesis in mitochondria of yeasts. Since these oxylipins accumulate in sexual cells (asci), increased mitochondrial activity is therefore expected in these structures. Strikingly, this assumption is supported in this study. Using selective fluorescence mitochondrial staining and CLSM, evidence is provided that mitochondrial function is much higher in asci containing increased amounts of 3-OH oxylipins compared to the corresponding asexual vegetative cells. Furthermore, when ASA, a mitochondrial inhibitor, was added in increased concentrations to cultures of Ascoidea, the sexual stage was found to be more sensitive. Ascospore liberation from asci was first inhibited followed by asci formation while some vegetative growth could still be observed.

Asetielsalisiensuur (ASA) sensitiewe 3-hidroksie (3-OH) oksilipiene is in 1991 ontdek in die gis Dipodascopsis uninucleata. Sedertdien is verskeie soortgelyke oksilipiene gevind in ‘n groot verskeidenheid fungi. Daar is bevind dat 3-OH oksilipiene ‘n rol speel in askospoorvrystelling vanuit ‘n verseëlde askus, waar hierdie oksilipiene betrokke is by verskillende nano-skaal ratagtige askospoorbewegings (D. uninucleata), askospoor glybewegings (Dipodascus), boor (Eremothecium sinecaudum) en prikbewegings (E. ashbyi en E. coryli). ‘n Oksilipien is ontdek in Ascoidea africana wat spesifiek geassosieer is met die hoedvormige askospore wat in ‘n ellipsoïedale askus gedra word. Die chemiese struktuur van hierdie komponent is 3-OH 10:1. In hierdie studie is geen funksie voorgestel vir dié oksilipien nie. Aangesien slegs een species van die genus Ascoidea ondersoek is, het dit die doel van hierdie studie geword om ook A. corymbosa en A. rubescens te ondersoek. Deur die gebruik van konfokale laserskanderingsmikroskopie op selle wat gekleur is met ‘n fluoresien-gekoppelde 3-OH spesifieke teenliggaam, was 3- OH oksilipiene duidelik om die askospore sigbaar, maar nie om die vegetatiewe selle of die askuswande van A. corymbosa en A. rubescens nie. Deur die gebruik van gaschromatografie-massaspektrometrie is die oksilipien 3-OH 17:0 ontdek. Hier word voorgestel dat die vlymskerp askospoorrante, wat bedek is met 3-OH oksilipiene, ‘n rol speel in die oopbreek van die askus tydens die geforseerde vrystelling van hoedvormige askospore uit die askus. Literatuur stel voor dat 3-OH oksilipiene in die mitochondria van giste deur ßoksidasie of vetsuursintese geproduseer word. Aangesien hierdie oksilipiene in geslagtelike selle (askus) akkumuleer, word verhoogde mitochondriale aktiwiteit in hierdie strukture verwag. Hierdie bewering word in hierdie studie 83 ondersteun. Deur die gebruik van ‘n selektiewe fluoresserende mitochondriale kleurstof en konfokale laserskanderingsmikroskopie, is bevind dat daar wel ‘n verhoogde mitochondriale funksie in die askus, met verhoogde hoeveelhede 3-OH oksilipiene in vergelyking met die ooreenstemmende vegetatiewe selle, is. Verder is ook bevind dat wanneer ASA, ‘n mitochondriale inhibitor, by die selle van Ascoidea in verhogende konsentrasies bygevoeg word, die geslagtelike fase meer sensitief was. Askospoorvrystelling vanuit die askus word eerstens geïnhibeer, dan opgevolg deur die inhibisie van askusvorming. Daar kan egter nog in sommige gevalle vegetatiewe groei waargeneem word.
Dissertation (M.Sc. (Microbial, Biochemical and Food Biotechnology))--University of the Free State, 2007
Keywords: Confocal laser scanning microscopy; Gas chromatography - mass spectrometry; Mitochondrial activity; Rhodamine 123; 3-hydroxy oxylipins; Yeast; Ascospore release; Ascoidea; Acetylsalicylic acid; Mictochondria; Lipids